Optimalisasi Guru dalam Membuat Media Pembelajaran untuk Mestimulasi Kemampuan Kognitif Anak Usia Dini - Pahenra Pahenra (Journal of Education and Teaching (JET), 2020)
The research objective was to determine the ability of teachers to create instructional media in stimulating the sensitivity of early childhood in PAUD Monapa, Palangga District, Konawe Selatan District. The subjects of this study were two teachers and the principal and the object was 15 students in group A. Data collection techniques used observation and interviews and documentation which were processed and analyzed through qualitative descriptive techniques. Description of the teacher's ability to make learning media in PAUD Monapa, Palangga District, Konawe Selatan Regency. The steps taken in making media are determining what media will be made, providing tools and materials, arranging steps for making media and how to convey it to students. The supporting factors are media that are made from scrap or used materials so that they are easy to get, while the inhibiting factor is that the school environment is still far from urban areas so it is difficult to get the tools used, but creative teachers use used materials or waste materials in making media and materials. this is very easy to get. The media created by the teacher aims to stimulate children's cognitive. Keywords: Teacher's Ability to Make Learning Media, Children's Cognitive